Beban Keluarga sebagai Caregiver Orang dengan HIV/AIDS - Darwita Juniwati Barus; Marthalena Simamora; Jek Amidos Pardede; Galvani Volta Simanjuntak (Politeknik Kesehatan Tanjung Karang, 2020)
The role of the family as a caregiver of people living with HIV/AIDS can cause a lot of stress. The purpose of this study was to explore the family burden as a caregiver of people living with HIV/AIDS. This research is qualitative research with a descriptive phenomenology approach. This research was conducted at RSUP H. Adam Malik in Medan City. Participants in this study were 4 family members who care for family members infected with HIV who were taken by purposive sampling technique. Participants' inclusion criteria were ≥17 years of age who were able to speak Indonesian and were able to tell about the burdens experienced while caring for people living with HIV/AIDS. The themes found included psychological burdens, social burdens, family problems, and role conflicts. The research conclusions illustrate that families who are caregivers in carrying out their roles are not easy because they cause psychological burdens, social burdens, economic burdens, family problems, and role conflicts. Nurses can provide nursing interventions to increase caregiver coping to reduce the burden they experience.